Implementation Of The Digital Financial Model For Islamic Boarding School Students As An Innovation In Student Financial Management - Beta Rohmaten; Nafi'ah Nafi'ah; Khoirul Fathoni; Nur Hidayah Izzati Binti Arba'in (JURNAL ECONOMINA, 2026)
Digital transformation in student financial management is analyzed in this study through the implementation of the Mondok Aja application at Pondok Pesantren Darul Falah Ponorogo to address the Society 5.0 era. The method employed was descriptive qualitative with a case study approach. Data collection was carried out through interviews, observation, and documentation involving Islamic boarding school administrators, students, parents, and application developers. Data analysis applied the Miles and Huberman interactive model, reinforced by the Technology Acceptance Model (TAM) perspective. The results of the study indicate that the Mondok Aja application has successfully transformed the financial management system of the boarding school to be more transparent, efficient, and secure through automated transaction logging and real-time balance monitoring. The presence of this system also established a user-centered financial ecosystem that contributes to improving students' financial literacy while strengthening collaboration between the school authorities and parents.